Influence of residential complex construction on the condition of the sewage collector and the underground water supply system in Kyiv on A. Barbyusa st. - Shuminskiy, Valerii; Stepanchuk, Serhiy; Dombrovskyi, Yaroslav; Kostetzkay, Svitlana; Kostochka, Yegor (Academic journal Industrial Machine Building Civil Engineering, 2018)
The article presents the design features of a residential complex located in the Barbyus street in Kyiv. The main city sewer and water supply is the basis of the residential designed complex. It is necessary to consider the possible impact of new residential complex construction on the sewer and water supply. To assess this effect, the stress-strain state in the soil around the collector and water supply system has been analyzed. Conclusions are drawn concerning the technical condition of the sewer and water supply system after residential complex construction and its further operation.